A qualitative exploration of the acceptability of a cognitive behavioural therapy self-help book for people with psychosis in Nicaragua. Issue 2 (3rd April 2022) - Lyons, Minna; Berrios, Roberto; Castro, Jorge; Castro, Sara; White, Ross G.; Brooks, Helen
ABSTRACT: Background: Cognitive Behavioural Therapy (CBT) self-help interventions have become a popular tool in High-Income Countries (HIC) to support people living with psychosis. There is limited research of this in Low– and Middle-Income Country (LMIC) contexts. We report findings of a qualitative investigation of a self-help book for psychosis in Nicaragua in Central America. Methods: Ten service users who self-identified as having psychosis were recruited from a mental health non-governmental organisation (NGO). Participants were given a Spanish version of a popular self-help book developed in the UK. They had four weeks to familiarise themselves with the book. Following this, we asked participants about their experiences of the book via an open ended questionnaire and a focus group discussion. Results: We conducted an inductive content analysis on the data. Evaluations of the book were positive. The book was considered easy to understand. The exercises were useful for coping with symptoms, as well as for recognising and managing relapse. Case studies were perceived useful in terms of reducing stigma and promoting self-acceptance. Discussion: The data highlight potential acceptability of CBT self-help books in the Nicaraguan context. We make recommendations for further research and evaluation to build on this signal of acceptability.